El valor de los Espacios Protegidos de montaña en un escenario de cambio global - Zamora, R.; Sánchez, F.J. (Ecosistemas, 2009)
Zamora, R., Sánchez, F.J. (2009). El valor de los Espacios Protegidos de montaña en un escenario de cambio global. Ecosistemas 18(3):35-37.